57.6: Stray Light Suppression for a Dual Depth HUD System. (4th October 2019) - Ma, Sen; Hong, Tao; Shi, Bingchuan; Li, Dianmeng; Wu, Naifu; Zhou, Chunmiao
Abstract : The stray light of a dual depth windshield type HUD prototype was analyzed from two aspects: the imaging quality and the heat received by the PGUs from the sun. The primary path of the stray light was found using the ray path function of Lighttools program, and stray light suppression design was performed based on the analysis results. The stray light was reanalyzed after stray light suppression design, and the results indicated that the imaging quality was improved and the heating effect on the PGUs from the sun was significantly reduced.